2021
DOI: 10.11648/j.ijcems.20210702.11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Hospital Attendance and Perceived Stigmatization Towards Individuals with COVID-19 Like Symptoms in Buea Municipality, Cameroon

Abstract: Objectives: The outbreak of COVID-19 has brought about fear and uncertainty resulting to stigmatization and discrimination towards those with COVID-19 like symptoms as well as influence the patient influx to health facilities and the health-seeking behaviour of the population. This study assessed the health-seeking behaviour, hospital attendance, and the level of stigmatization of the population towards individuals with COVID-19 like symptoms. Methods: This was a cross-sectional community and hospital-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Symptoms not being severe and fear of stigmatization were the major reasons of not seeking care from the hospital. The plausible explanation could be due to the fact that a great majority of the cases in our study were asymptomatic patients who literally had no life threatening symptoms hence felt no need for hospital consultation; also we recruited patients at the peak of the pandemic when there was still a lot of myths about COVID-19 with patients having COVID-19 symptoms being regarded as those who were going to die soon and would be neglected this findings are in line with that of Tendengfor et al, [12].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Symptoms not being severe and fear of stigmatization were the major reasons of not seeking care from the hospital. The plausible explanation could be due to the fact that a great majority of the cases in our study were asymptomatic patients who literally had no life threatening symptoms hence felt no need for hospital consultation; also we recruited patients at the peak of the pandemic when there was still a lot of myths about COVID-19 with patients having COVID-19 symptoms being regarded as those who were going to die soon and would be neglected this findings are in line with that of Tendengfor et al, [12].…”
Section: Discussionsupporting
confidence: 84%
“…With the occurrence of a global pandemic of this nature associated with fear of the outcome when one gets infected the Health seeking behaviour could be greatly hampered ; the outbreak of the SARS in Hong Kong that occurred in 2003 was associated with a lot of hospital avoidance [9]. The mental or brain health impacts of the COVID-19 pandemic are evident in Cameroon [10], but the impact of the preventive measures on mental health is still not well understood .Many studies have examined healthcare utilization using Andersen's behavioral models, where various multidimensional factors determine healthcare-seeking behaviors of people including predisposing factors (age, gender, ethnic, cultural, social), enabling factors (financial, insurance coverage, healthcare accessibility, healthcare availability), and need factors (health perceptions, medical conditions) [11].The first case of COVID-19 was reported in Buea south west region of Cameroon in the early days of April 2020 associated with a lot of misinformation, fear and stigmatization towards individuals who tested positive for COVID-19 [12].The majority of cases diagnosed from the lone treatment center in the early months of the pandemic were mainly asymptomatic cases and studies have proven that this group of persons are carriers and there is a possibility of transmitting and infecting the population [13]. Systematic reviews have reported expected psychological and mental health problems due to the outbreak of COVID-19, such as stress, anxiety, depressive symptoms, insomnia, denial, stigma ,anger and fear [14].…”
Section: Introductionmentioning
confidence: 99%